Doing theology in a globalized world: religion, diversity and conflicts in films - Gräb, Wilhelm (Religion, diversity and conflict, 2011)
This essay refers to God-Talk as rejlection about lived religion in a media age. Threefilm-"Cast away," "As it is in Heaven, "and "Babel" -are analyzed in order to illustrate forms ofGod-Talk in modern media. Watchingjilms may stimulate spiritual experiences and theological rejlections. /fit is true that because of a spiritual need and a need for God-Talk every human being is motivated to theological rejlection-because the quest about the last unconditional meaning of life is imposed on all of us-films open up a wide range of theological thinking. The question is whether the framework of Christian tradition provides sufficient room for theological rejlection. Popular culture has developed its own rejlective framework and basic thinking about fundamental human issues. Films may create a new understanding of these topics. The pluralism that confronts the cinema-goer differs from the uniformity of the belief-system which the traditional church-goer faces. To be in dialogue with others' world views, cultures, languages and theological frameworks of thinking is one of the most compelling challenges in the globalized world of today.